Metaphors and Idioms of Wayang Tradition: A Dialogue Between Javanese Literature and Islamic Character Values - Tricahyo, Agus; Nursalam, Yufridal Fitri (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2025)
This study explores the use of metaphors and idioms in Wayang, a traditional Javanese art form, and its potential to convey Islamic character values. The research analyzes five popular Wayang plays, namely Banjaran Noroyono, Banjaran Bima, Wiratha Parwa, Wahyu Makutha Rama, and Babat Wanamerta, to identify and categorize various metaphorical and idiomatic expressions. The study employs a qualitative approach using an inductive method that involves the observation of Wayang performances, examination of corresponding manuscripts, and systematic documentation of metaphorical and idiomatic structural units. The analysis revealed 52 patterns of metaphors and idioms encompassing figurative, personification, simile, verbal, phrase, sentence, and adjectival idioms. These expressions convey a wide range of meanings, from descriptive phenomena and social values to complex concepts, such as hedonism, pessimism, and domestic issues. Moreover, metaphors and idioms reflect diverse character traits, including responsibility, courage, patriotism, honesty, and humility, which align with Islamic teachings. This study highlights the potential of Wayang metaphors and idioms to enrich dialogue between Javanese culture and Islamic values, fostering tolerance, inclusivity, and cultural preservation in the era of globalization. Despite the limitations of focusing on the five selected plays, the research underscores the significance of harmonizing religious and cultural values to promote a more civilized society.